Web Based Sales Information System Using the Waterfall Method for Cashier and Product Management - Awaluddin; Muhammad Fadhil Mu’min; Riandy; Syahril Ramadhan; Muhammad Nur Faiz; Ahmad Khairul Shiddiq (Academic Bright Collaboration, 2025)
This article presents the development of a web based sales information system for e commerce named Comerch using the Waterfall method. E commerce offers convenient online transactions yet imposes challenges in managing complex sales processes. The study aims to design and implement a system that supports transaction processing, product management, and an accessible and efficient platform. The Waterfall stages applied include requirements analysis, system design, coding, integration, and testing. Findings show that Waterfall enabled a structured and efficient development pipeline and smooth integration of system components. The resulting system provides core functions including product management, payment transactions, and real time reporting which improve operational efficiency and user experience. Scenario based testing confirms that the system performs as expected. Black box testing across forty six scenarios achieved one hundred percent functional validation. The study contributes a practical reference for developing sales information systems for small and medium enterprises and for practitioners seeking predictable and well documented development cycles.